Profile of an occupation – plant mechanic for sanitary, heating and air conditioning systems - Schambeck, Arne [Verfasser] (My University, 2023)
"The transition to sustainable heating energy proclaimed by policy makers is putting wind into the sails of an occupation which has long since had a “rock bottom” reputation among young people. The chance to become involved with a diverse range of modern technologies is making the training occupation of plant mechanic for sanitary, heating and air conditioning systems more and more popular and is helping bring about an image shift. This article describes the state-of-the-art and energy-efficient systems being used in technical building equipment plants and also looks at the development in trainee numbers." (author's abstract; BIBB-Doku)
Keywords: S 6.2.7 Ausbauberufe; 370; Anlagenmechaniker für Sanitär-, Heizungs- und Klimatechnik; Berufsbild